The first report of Lasioderma Serricorne infestation on dried fish crackers in Malaysia - Azmiera N.,; Singh S.,; Heo, C. C. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper is the first record of cigarette beetles collected from dried fish crackers (also known as “keropok ikan” in Malay) in Malaysia. The dead cigarette beetles were firstly isolated from a packet of dried fish crackers and were subsequently kept in 70% ethanol. The beetles were then identified as Lasioderma serricorne (Fabricius 1792) (Coleoptera: Anobiidae). They are common pests of stored products such as tobacco, flour, and cocoa beans but there is no record of this beetle infestation on dried fish crackers in Malaysia.